Problems of preparing students for craft activities in the system of vocational education and its current state - Atajanova Dilarom (Indonesian Journal of Innovation Studies, 2022)
This article describes the state support of artisans, the benefits created for them and the work done by artisans, the problems that need to be addressed in vocational guidance, the conditions in the "Teacher-Apprentice" schools, practical assistance to young people in learning a profession.